Screening and characterization of sponge-associated bacteria from Seribu Island, Indonesia producing cellulase and laccase enzymes - WENANG MAHARSIWI; RIKA INDRI ASTUTI; ANJA MERYANDINI; Aris Tri Wahyudi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Maharsiwi W, Astuti RI, Meryandini A, Wahyudi AT. 2020. Screening and characterization of sponge-associated bacteria from Seribu Island, Indonesia producing cellulase and laccase enzymes. Biodiversitas 21: 975-981. Exploration of new enzymes from an extreme environment is important to improve industrial efficiency. This study aimed to get sponge-associated bacteria from Seribu Island with the capability to produce cellulase and laccase. These enzyme activities were indicated by the clear zones on CMC medium for cellulase and the reddish-brown zone on Guaiacol medium for laccase. About 100 of sponge-associated bacteria have been isolated from 5 marine sponges used SWC and NA modified media. As screened, one isolate (AGN89) could produce both enzymes and 11 isolates could produce cellulase. Quantitative analysis was performed using the DNS method and obtained the activities of 4 best cellulolytic isolates ranged from 0.04-0.06 UmL-1 and 0.70-1.18 UmL-1 in enzyme and specific activities, respectively. Gene-based determination for the isolate producing laccase resulted in a ±1100 bp amplicon fragment which identified as multicopper oxidase family protein. Based on the 16S-rRNA gene, AGN89 and these 4 cellulolytic isolates were identified as Pseudomonas luteola strain NBRC 103146, Bacillus aerius strain 24k, Pseudomonas aeruginosa strain DSM 50071, Mycobacterium maritypicum strain DSM 20578, and Brachybacterium conglomeratum strain J 1015. This result suggests that the sponge-associated bacteria from Seribu Island could become new enzymes producer for further applications in industry.